Dynamic control strategy for the electrolyte flow rate of vanadium redox flow batteries. (1st October 2018) - Wang, Tao; Fu, Jiahui; Zheng, Menglian; Yu, Zitao
Highlights: A transient model of the VRB system is developed. The model is used for dynamic control for electrolyte flow rate of VRB. Flow rate is optimized under varying (dis-)charge power and SoC conditions. Concentration discrepancy of active species in the stack and tank is considered. Relatively low electrolyte flow rates are preferred with high pressure drops. Abstract: The vanadium redox flow battery (VRB) is considered to be one of the most promising technologies for large-scale energy storage, with the electrolyte flow rate capable of significantly affecting the mass transfer, temperature rise, and pump power losses of the VRB system. Although the flow-rate optimization under constant current has been addressed in the literature, few studies have investigated the control strategy for the electrolyte flow rate under varying (dis-)charge power that is common in practical applications. Moreover, fewer studies have considered the concentration discrepancy of the active species in the tank and stack in the flow-rate optimization. In this paper, the electrolyte flow-rate optimization is investigated by incorporating the influences of the flow rate on the mass transfer, temperature rise, and required pump power. A transient model of the VRB system is developed to derive the total power losses (by which the overall system energy efficiency is determined; include losses resulting from overpotentials, ohmic drops, and required pump power) as a function of the applied current, concentration of the active species in the stack, and flow rate of the electrolyte. Based on this model, a dynamic flow-rate control strategy is proposed for determining the optimal flow rate under varying (dis-)charge power and state-of-charge conditions. The simulation results show that the proposed control strategy can deliver a high VRB system efficiency of 87.7%, and manage the electrolyte temperature to the safe range during mild summer days.